2018
DOI: 10.1080/09286586.2018.1441426
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of trachoma in Yemen: results of population-based prevalence surveys of 42 evaluation units in nine governorates

Abstract: Purpose: In suspected trachoma-endemic areas of Yemen, we sought to determine the prevalence of the sign trachomatous inflammation-follicular (TF) in children aged 1-9 years, and the potential individual and household risk factors for TF in that age group. We also sought to determine the prevalence of trichiasis in adults aged ≥15 years. Methods: We conducted a cluster-sampled survey in each of 42 evaluation units (EUs) comprising 166 rural districts of nine Governorates (Adh Dhale'a, Al Hodeihah, Al Jawf, Had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(21 reference statements)
2
8
0
Order By: Relevance
“…In adults aged ≥15 years, trichiasis prevalence was ≥0.2% in five EUs (19 districts). The surveys revealed that more than 2.7 million people in 30 districts need publichealth interventions to deal with transmission of the trachoma and its associated morbidity [10]. Also, in a study by Al-Shamahi et al [9], the prevalence of active trachoma (TF) was 10.93%, which is slightly higher compared to the previous study conducted in Yemen [10].…”
Section: Introductionmentioning
confidence: 91%
“…In adults aged ≥15 years, trichiasis prevalence was ≥0.2% in five EUs (19 districts). The surveys revealed that more than 2.7 million people in 30 districts need publichealth interventions to deal with transmission of the trachoma and its associated morbidity [10]. Also, in a study by Al-Shamahi et al [9], the prevalence of active trachoma (TF) was 10.93%, which is slightly higher compared to the previous study conducted in Yemen [10].…”
Section: Introductionmentioning
confidence: 91%
“…In adults aged≥15 years, trichiasis prevalence was ≥0.2% in five EUs (19 districts). The surveys revealed that more than 2.7 million people in 30 districts need public-health interventions to deal with transmission of the trachoma and its associated morbidity 10 . Also, in a study by Al-Shamahi et al, 9 , the prevalence of active trachoma (TF) was 10.93%, which is slightly higher compared to the previous study conducted in Yemen 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Trachoma is the leading cause of infectious blindness in the world, and loss of infrastructure in Yemen has allowed trachoma to thrive. While conflict has prevented surveillance over some rural areas, data collected by Ali Thabit et al 24 and the Global Trachoma Mapping Project estimate 2.5 million people are at risk in Yemen 25. This mapping aided a successful large-scale treatment campaign of medicines and equipment following WHO’s recommended SAFE strategy (Surgery, Antibiotics, Facial cleanliness and Environmental improvement), highlighting the importance of accurate health information in disease treatment.…”
Section: Analysis Of Eye Health Servicesmentioning
confidence: 99%